Genetically predicted the causal relationship between gut microbiota and the risk of polymyositis/dermatomyositis: a Mendelian randomization analysis - Niu, Yanna; Zhang, Yaochen; Fan, Keyi; Hou, Jialin; Liu, Liu; Zhang, Heyi; Geng, Xinlei; Ma, Xiyue; Lin, Shilei; Guo, Meilin; Li, Xiaofeng; Zhang, Shengxiao (Frontiers in Microbiology, 2024)
Observational studies suggest associations between gut microbiota and polymyositis (PM) and dermatomyositis (DM), but causal relationships are unclear. We investigate the causal effects of gut microbiota on PM and DM, providing insights hoping to provide insights for future treatment and prevention. Summary statistics of gut microbiota were obtained from a multi-ethnic Genome Wide Association Studies (GWAS) meta-analysis, including 119 taxa from 18,340 Europeans. PM/DM statistics were extracted from GWAS analyses. Mendelian randomization (MR) with IVW, MR-Egger, and weighted median methods was performed. Sensitivity analyses addressed heterogeneity and pleiotropy. Of the 119 bacterial genera studied, six showed causal links. Alloprevotella (OR: 3.075, 95% CI: 1.127-8.386, P=0.028), Ruminococcaceae UCG003 (OR: 4.219, 95% CI: 1.227-14.511, P=0.022), Dialister (OR: 0.273, 95% CI: 0.077-0.974, P=0.045) were associated with PM. Anaerotruncus (OR: 0.314, 95% CI: 0.112-0.882, P=0.028), Ruminococcaceae UCG002 (OR: 2.439, 95% CI: 1.173-5.071, P=0.017), Sutterella (OR: 3.392, 95% CI: 1.302-8.839, P=0.012) were related to DM. Sensitivity analyses validated these associations. We establish causal relationships between Ruminococcaceae, Sutterella, Anaerotruncus with DM, Alloprevotella, Ruminococcaceae UCG003, and Dialister with PM.Common microbiota, like Ruminococcaceae, have significant clinical implications. These findings open up greater possibilities for the gut microbiota to contribute to the development of PM / DM and for future monitoring of the gut microbiota in patients with PM / DM.